2021
DOI: 10.1088/1755-1315/676/1/012027
|View full text |Cite
|
Sign up to set email alerts
|

On Strategies of Residential Indoor Healing Landscape Construction under the Era of Epidemic

Abstract: The indoor healing landscape has a positive influence on people’s mind and physical health, indicated from the studies. This research aims to discuss the residents’ emotional problems during the home quarantine under the context of COVID-19 and put forward the strategies to construct a residential indoor healing landscape system based on disaster psychology, which is conducive to relieve residents’ emotional problems. Firstly, the general introduction includes the adverse effects on residents’ minds and physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 3 publications
0
14
0
Order By: Relevance
“… Health Protection Physical Health [1] , [2] , [3] , [4] , [6] , [7] , [8] , [11] , [12] , [13] . Mental Health [2] , [4] , [9] . Get work done and succeed [1] , [4] , [8] , [13] .…”
Section: Stay Home: Implications and Causesmentioning
confidence: 99%
See 4 more Smart Citations
“… Health Protection Physical Health [1] , [2] , [3] , [4] , [6] , [7] , [8] , [11] , [12] , [13] . Mental Health [2] , [4] , [9] . Get work done and succeed [1] , [4] , [8] , [13] .…”
Section: Stay Home: Implications and Causesmentioning
confidence: 99%
“…The spread of the Coronavirus posed a great threat to human physical and mental health. As studies showed, staying home exacerbated its occupants’ physical and mental pressure [9] . A. Kaklauskas et al explained that social isolation had hit the population’s mental and physical health [6] .…”
Section: Stay Home: Implications and Causesmentioning
confidence: 99%
See 3 more Smart Citations